Innate local response and tissue recovery following application of high density microarray patches to human skin - Muller, David A. (Sci Rep, 2020)
The development of microarray patches for vaccine application has the potential to revolutionise vaccine delivery. Microarray patches (MAP) reduce risks of needle stick injury, do not require reconstitution and have the potential to enhance immune responses using a fractional vaccine dose. To date, the majority of research has focused on vaccine delivery with little characterisation of local skin response and recovery. Here we study in detail the immediate local skin response and recovery of the skin post high density MAP application in 12 individuals receiving 3 MAPs randomly assigned to the forearm and upper arm. Responses were characterised by clinical scoring, dermatoscopy, evaporimetry and tissue viability imaging (TiVi). MAP application resulted in punctures in the epidermis, a significant transepidermal water loss (TEWL), the peak TEWL being concomitant with peak erythema responses visualised by TiVi. TEWL and TiVi responses reduced over time, with TEWL returning to baseline by 48 h and erythema fading over the course of a 7 day period. As MAPs for vaccination move into larger clinical studies more variation of individual subject phenotypic or disease propensity will be encountered which will require consideration both in regard to reliability of dose delivery and degree of inherent skin response.